Air combat model engagement and attrition processes high level design - Allen, Patrick D.; Project Air Force (U.S.). Force Modernization and Employment Program; Arroyo Center; Rand Corporation; United States. Air Force; United States. Army. (Santa Monica, CA : RAND, 1993)
This Note presents the high-level design document for air combat (engagement and attrition processes) for the theater-level or nonlinear combat (TLC/NLC) model and possibly, for the RAND Strategy Assessment System (RSAS). The design includes many qualitative factors not traditionally included in previous air combat models, such as a representation of how intelligence affects the frequency and distribution of specific types of air-to-air, ground-to-air, and air-to-ground engagements. The design is intended to be implemented as either a stochastic or a deterministic model, with either low resolution or high resolution, depending on the needs of the user. Thus, the model is being designed so that each version will be readily comparable given similar inputs. The document describes the three main parts of the overall air combat assessment process: (1) determine whether or not penetrators are detected before reaching in engagement zones; (2) determine the sequence of ground-to-air, air-to-air, and air-to-ground engagements; and (3) assess air-to-air, ground-to-air, and air to ground engagements in sequence determined for ingress and egress.
Research "was conducted jointly under the Force Employment Program of Project Air Force, and by the Army Research Division's Arroyo Center"--Preface.
Includes bibliographical references (p. 57).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Air defenses -- Computer simulation; Combat -- Computer simulation; Fighter plane combat -- Computer simulation